General Ordinances of the City of Plainfield, New Jersey 125-26 (1902) - (:unkn) unknown (My University, 1895)
An Ordinance Concerning Firearms and Other Deadly Weapons: That no person shall fire or discharge any gun, fowling piece or firearms within the limits of the City of Plainfield. That no person shall carry within the limits of the City of Plainfield concealed upon or about his person, any pistol, dirk, butcher or bowie knife, stilletto, dagger, sword, or spear in a cane, brass or metal knuckles, razor, slug shot, or other deadly weapon
Keywords: CARRY - CONCEALED; DISCHARGE